2012
DOI: 10.5301/hip.2012.9576
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcome after Infection of Megaprostheses

Abstract: Recent advances in chemotherapy and radiation therapy in the treatment of malignant bone tumours as well as the consistent increase of revision arthroplasties have been followed by an increased use of megaprostheses. These large foreign bodies make infection a common and feared complication. Infection rates of 3 - 31% have been reported (average approx. 15%), often in conjunction with risk factors, e.g. the anatomic region (pelvis implants in particular), implant alloy, and underlying reason for implantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
22
0
3
Order By: Relevance
“…A recent study by Jansen et al reported a high risk of complications and poor long-term function in patients following acetabular reconstruction with saddle prostheses after peri-acetabular tumour surgery [15]. Another technique of endoprosthetic restoration, especially in relation to reconstruction of extended pelvic defects in cases of primary malignant tumours or solitary metastatic bony lesions of the pelvis, is the internal hemipelvectomy and reconstruction with an endoprosthetic pelvic replacement [9,[16][17][18][19]. Although this technique, first described in 1978, has been improved due to the possibility of exact planning of resection and construction of the implants using threedimensional imaging, the functional outcome has been described as limited to poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Jansen et al reported a high risk of complications and poor long-term function in patients following acetabular reconstruction with saddle prostheses after peri-acetabular tumour surgery [15]. Another technique of endoprosthetic restoration, especially in relation to reconstruction of extended pelvic defects in cases of primary malignant tumours or solitary metastatic bony lesions of the pelvis, is the internal hemipelvectomy and reconstruction with an endoprosthetic pelvic replacement [9,[16][17][18][19]. Although this technique, first described in 1978, has been improved due to the possibility of exact planning of resection and construction of the implants using threedimensional imaging, the functional outcome has been described as limited to poor.…”
Section: Discussionmentioning
confidence: 99%
“…Although this technique, first described in 1978, has been improved due to the possibility of exact planning of resection and construction of the implants using threedimensional imaging, the functional outcome has been described as limited to poor. Furthermore, this technique seems to be associated with a high incidence of postoperative complications, such as deep infection and dislocation [9,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the literature shows that besides the occurrence of a local recurrence, periprosthetic infection remains the most serious complication following limb salvage procedure with megaprosthesis. 37,6,38 Infection of a megaprosthesis ( Fig. 2) implanted following tumor resection leads to major morbidity and sometimes amputation.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%
“…the anatomic region (pelvis implants in particular), implant alloy, and underlying reason for implantation of a megaprosthesis. 37 The rate of infections varies according to the site of replacement with lower rates in upper extremities and higher rates in lower extremities. [39][40][41][42][43][44] However postsurgical infection is more common in pelvic tumor surgeries.…”
Section: Custom-made Megaprosthesismentioning
confidence: 99%
See 1 more Smart Citation